PERANAN LITERASI SAINS DALAM PEMBELAJARAN FISIOLOGI TUMBUHAN - I Made Subrata; I Gusti Ayu Rai (Widyadari : Jurnal Pendidikan, 2022)
Scientific literacy plays a role as scientific knowledge and skills to be able to identify questions, acquire new knowledge, explain scientific phenomena, and draw conclusions based on facts, understand the characteristics of science, awareness of how science and technology shape the natural, intellectual, and cultural environment, as well as the willingness to be involved and concerned with science-related issues. Science plays an important role in the development of Science and Technology, therefore scientific literacy needs to be introduced from an early age and taught in primary, secondary and higher education so that knowledge, understanding, and science skills are embedded in children, both in the form of critical thinking skills, hard skills as well as soft skills. Scientific literacy is required in various branches of science. Learning Plant Physiology which is one part of the biological sciences, the inclusion of scientific literacy is a necessity, so that the Learning Outcomes of Courses (CPMK) and Graduate Learning Outcomes (CPL) are maximized. Improving scientific literacy in plant physiology learning can be applied through various innovative learning models including: (1) Project Based Learning (PjBL) learning model, (2) Problem Based Learning (PBL) learning model, (3) Experimental learning model to explore the surrounding environment ( EJAS), (4) Discovery Learning model, (5) Service Learning model, (6) Inquiry learning model. All of these learning models are constructivist, so they can improve critical thinking skills, problem solving skills, higher order thinking skills and the ability to interact socially humanities